Design and development of a chamotte for use in a low-clay translucent whiteware - Capoglu, A; Messer, PF (Elsevier Sci Ltd, 2004)
In the design of a translucent whiteware it was intended to combine the best features of bone china and hard porcelain, i.e. to be aesthetically pleasing and to have the resistance to edge chipping of the former with the scratch resistance of the type of glaze used on the latter. The design envisaged producing a whiteware from two chamottes, each having the same composition but with different median particle sizes, and only a small amount of clay (similar to10 to 15%) to minimise the firing shrinkage and its anisotropy. In the design of the chamotte composition. anorthite ((CaOAl2O3)-Al-..2SiO(2)) was selected to be the major phase and inullite (3Al(2)O.2-SiO2) and glass the minor phases. A further design requirement was to have high crystalline (greater than or equal to70%) and low glass (less than or equal to30%) contents to enhance the fracture toughness of the whiteware. Anorthite was chosen as the major phase because its refractive index would be similar to that of the glass phase, which enhances translucency, and its thermal expansion coefficient (TEC) allows the TEC of the whiteware to match that of sonic glazes made with high-silica contents. Mullite was found to reduce sagging during glost firing. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: anorthite; mullite; prefiring; translucent whiteware; whiteware